2017
DOI: 10.4049/jimmunol.1700024
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Small Molecule Disruption of the AID/RAD51 Axis Similarly Protects Nonobese Diabetic Mice from Type 1 Diabetes through Expansion of Regulatory B Lymphocytes

Abstract: B-lymphocytes play a key role in type 1 diabetes (T1D) development by serving as a subset of APC preferentially supporting expansion of autoreactive pathogenic T-cells. As a result of their pathogenic importance, B-lymphocyte-targeted therapies have received considerable interest as potential T1D interventions. Unfortunately, B-lymphocyte-directed T1D interventions tested to date failed to halt β-cell demise. IgG autoantibodies marking humans at future T1D risk indicate B-lymphocytes producing them have underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…Furthermore, AID deficiency may also enhance the escape of these pathogenic B cell clones from GCs of peripheral lymphoid tissues by evading the selection pressures and circulating to target the systemic host organs (39). AID (23), in which the results obtained could be due to the different approach used for genetic targeting and a different environment. Foxp3 + Tregs were also not affected here by AID deficiency in our model system.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, AID deficiency may also enhance the escape of these pathogenic B cell clones from GCs of peripheral lymphoid tissues by evading the selection pressures and circulating to target the systemic host organs (39). AID (23), in which the results obtained could be due to the different approach used for genetic targeting and a different environment. Foxp3 + Tregs were also not affected here by AID deficiency in our model system.…”
Section: Discussionmentioning
confidence: 94%
“…6G). We recently found that partially overlapping populations of CD73 expressing and IL-10 producing Bregs can inhibit autoimmune T1D development in NOD mice (44). Ablation of Nfkbid also reduced levels of such IL-10 producing and CD73 expressing Bregs in NOD mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The administration of an IL-10 neutralizing antibody (JES5-2A5) in NOD mice following transient BAFFR-Fc treatment abrogated the T1D protective effects of this reagent (Figure 4H). We recently identified a subset of CD73 + B-lymphocytes capable of suppressing the activity of NOD diabetogenic T-cells (29). Thus, we characterized the extent B-lymphocytes expressed CD73 following the various depletion regimens.…”
Section: Resultsmentioning
confidence: 99%
“…T1D resistance elicited in NOD mice by transient BAFFR-Fc treatment also coincided with an initial expansion of a CD73 + B-lymphocytes. We recently found B-lymphocytes in NOD- Aicda null mice convert to a CD73 + phenotype capable of suppressing diabetogenic T cell responses through production of immunosuppressive adenosine (29). However, following cessation of treatment, proportions of CD73 + B-lymphocytes do not remain expanded in NOD mice in which long term T1D resistance was established by transient BAFFR-Fc mono-therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation